Quality by Design: Development of the Quality Target Product Profile (QTPP), Critical Quality Attributes (CQAs), Critical Material Attributes (CMAs) and Critical Process Parameters (CPPs) for Transdermal Drug Delivery Systems - C. Pandian; Praveen Kumar D; Gowtham A; Pooja B; Gunaseelan M; Keerthana M (International Journal of Pharmaceutical Sciences and Medicine, 2026)
The quality by design (QbD) paradigm has been the accepted model for building quality into pharmaceutical products rather than testing it in retrospectively. The systematic application of QbD to transdermal pharmaceutical delivery systems (TDDS) is relatively underdeveloped in the literature despite the growing commercial and clinical relevance of the dosage form, although QbD has been widely articulated for oral solid dosage forms and more recently for semisolid topical products. Transdermal patches present a different set of engineering and biopharmaceutical challenges (adhesive performance over multi-day wear, matrix mechanical integrity, controlled permeation flux across the stratum corneum, dimensional/content uniformity from continuous casting or coating processes, etc.) that are substantially different from oral or semisolid dosage forms. This review defines and consolidates a quality target product profile (QTPP) framework for TDDS, identifies the critical quality attributes (CQAs) that determine patch performance and patient acceptability, and maps these to the critical material attributes (CMAs) of the drug substance, polymers, plasticizers, permeation enhancers and adhesives, as well as the critical process parameters (CPPs) of casting, coating, drying, lamination and die-cutting operations that govern them. A risk based summary of possible failure modes is presented and the practical extension of this framework to vesicular carrier based transdermal systems such as niosomal patches is briefly discussed.